APPLIED PHOTOVOICE IN CRIMINAL JUSTICE voices made visible. - Fitzgibbon, Wendy ([S.l.] : ROUTLEDGE, 2022)
Building on her leading research in creative methodology, in this book Wendy Fitzgibbon explores and illustrates how Photovoice, a participatory, active research tool, can enable new insights and engagement with both marginalised people and those working with them in the criminal justice system. Including research examples from criminal justice settings around Europe, the book explains how one could undertake such research and the ethical and practical challenges presented.Engaging, accessible and illustrated with original photographs, this book not only presents the theoretical and practical information necessary for researchers, students and practitioners to be able to utilise Photovoice - it demonstrates these with original empirical findings from an international range of projects, including work with the probation service, with female offenders and with an open prison. It is essential reading for those engaged with criminological research methods, and Visual Criminology.
Keywords: Criminal justice, Administration of -- Research -- Methodology; Criminology -- Research -- Methodology; Participant observation; Action research -- Methodology; SOCIAL SCIENCE / Criminology